Battery States Controlling via PV-Wind Hybrid System - Bhardwaj, Vikash; Ahmed, Husain (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
With increasing demand of energy and shortage of conventional sources renewable energy sources are used for environmental concerns. In this paper an integrated system of a wind-PV generating system connected to a battery and load is proposed. Being complimentary in nature, continuous power ability can be obtained from PV and wind system. Main issue in distributed generation is power quality and harmonics etc. In the proposed system PV-wind system draw is the load and battery charging, while the supply from PV-wind system is low, battery draw is the load. The system is modeled and analyzed in MATLAB / SIMULINK. The wind turbine draws wind generator and a bridge rectifier is used for DC conversion. The PV variable DC output is fed to boost converter and maximum power point is tracked by MPPT. PV-wind systems are combined to operate in parallel and total energy is collected and used to draw DC load and to charge battery partly. In the proposed system a useful wind PV model is offered for performance analysis of such a system.